ETIKA BISNIS DALAM PERSPEKTIF ISLAM : EKSPLORASI PRINSIP ETIS AL QUR’AN DAN SUNNAH (UINSI Samarinda, 2013)
Business is something that is very important in human life. No wonder Islam is rooted in the Qur'an and Sunnah provide guidance in the field of business. Business for many years, was suggested as a business for profit as much as possible, even to go to the dirty tricks and unethical. Business ethics is very important to put forward in the era of globalization often ignore the moral values and ethics. Thus, Islam emphasizes that the business activities of human beings are not merely intended as a way to satisfy the desire, but rather on finding a balanced life with a positive attitude rather than destructive. This paper aims to examine business ethics from the perspective of the Qur'an in an effort to build an Islamic business to business challenges in the future. Business in the conclusion of the Qur'an called activities as well as materials. A viable business, if they meet the material and spiritual needs in a balanced, contains no falsehood, destruction and injustice. But it contains the value of unity, equilibrium, free will, accountability, truth, virtue and honesty.